2003
DOI: 10.1046/j.1440-1754.2003.00266.x
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary function and scoliosis in children with spinal muscular atrophy types II and III

Abstract: This study suggests that pulmonary function in SMA types II and III continues to decline after scoliosis surgery, though the rate of decline is less marked. Overall, the combined results from this study and all other previously published studies are conflicting in regard to the effect of scoliosis surgery on pulmonary function in SMA types II and III, though half of the studies (3 of 6) did demonstrate a continued decline in lung function postoperatively. This decline in pulmonary function despite spinal stabi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
40
0
8

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(49 citation statements)
references
References 18 publications
1
40
0
8
Order By: Relevance
“…Other studies have shown that an average correction of 40-64% in spinal curvature can be achieved, without much progression in the curve postoperatively [11,32,35]. Scoliosis in patients with flaccid neuromuscular pathology (DMD and SMA) is actually a kypho-scoliosis deformity, in comparison to other forms of neuromuscular scoliosis with spasticity where lumbar lordosis is usual [47].…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have shown that an average correction of 40-64% in spinal curvature can be achieved, without much progression in the curve postoperatively [11,32,35]. Scoliosis in patients with flaccid neuromuscular pathology (DMD and SMA) is actually a kypho-scoliosis deformity, in comparison to other forms of neuromuscular scoliosis with spasticity where lumbar lordosis is usual [47].…”
Section: Discussionmentioning
confidence: 99%
“…However, the severity of progression of scoliosis and pelvic obliquity seems more pronounced in SMA II than in SMA IIIa [44]. Studies on the course of pulmonary function after surgery for scoliosis are conflicting and seem to confirm a progressive decline in lung function despite spinal stabilization due to the progressive neuromuscular weakness associated with the disease [45].…”
Section: Scoliosismentioning
confidence: 99%
“…While numerous reports are available on respiratory involvement in Duchenne Muscular Dystrophy (DMD) or Spinal Muscle Atrophy (SMA) [1][2][3][4][5][6][7] only few studies have focused specifically on slowly progressive neuromuscular disorders such as Limb-Girdle Muscular Dystrophy (LGMD), Becker Muscular Dystrophy (BMD) and FacioScapulo Humeral Dystrophy (FSHD). LGMD patients generally show a mild global respiratory muscle weakness that usually affects expiratory more than inspiratory muscles, in the absence of significant involvement of the diaphragm [8,9].…”
Section: Introductionmentioning
confidence: 99%